Determinantes de localização subnacional do investimento direto estrangeiro em economias emergentes - Izumi, Paulo Kazuhiro (2019)
The shift in the locational pattern of foreign direct investment towards emerging economies has generated a growing interest of international business research. At the same time, the literature increasingly recognizes that the nation as a unit of analysis is rather limited and now considers subnational places as a more appropriate level for examining multinational enterprise strategies. The purpose of this thesis is to identify and estimate the determinants of the subnational location of foreign direct investment in emerging economies. Based on contributions from international business, new economic geography, and institutional theory, the research uses an integrated conceptual framework to assess the impacts of a set of firm-level, host-country and subnational-level advantages on location in global cities of emerging economies. From a sample of 982 foreign subsidiaries of Japanese multinationals established in countries in Africa, Europe, Latin America and Oceania, the results of the application of multinomial logistic regression models showed that the global cities of emerging economies have a strong attraction for investment. The size of the subsidiaries is inversely proportional to the location in the global city hierarchy. More experienced and service-based subsidiaries are prone to locate within global cities, as opposed to the less experienced manufactures, which tend to settle in peripheral cities. The main sub-national determinants are the locational advantages related to market size and potential market demand, evidencing differences between global cities of the South and their congeners in advanced economies. The ease of doing business in countries and regulatory complexity exert a centrifugal force, driving investment out of global cities. The study contributes to international business literatures, economic geography, and institutional theory by demonstrating that the city is the most relevant unit for global FDI localization strategies and subnational institutional heterogeneity has an impact on these decisions. Attributes of cities in emerging economies, even under the label of global cities, are specific and their effects on the behaviour of the multinational enterprise must be evaluated particularly. The study enriches our understanding of the locational determinants of foreign direct investment and transposes the existing literature by focusing on the subnational context in emerging economies.